Trajectories of Quality of Life and Associated Risk Factors in Patients With Knee Osteoarthritis: Findings From the Osteoarthritis Initiative. (September 2018) - Han, Alex; Gellhorn, Alfred C.
Abstract : Objective: Knee osteoarthritis (OA) has a significant impact on quality of life (QOL). Although QOL is generally thought to diminish over time, it is unknown whether different patient groups demonstrate unique patterns of change in QOL. We sought to identify and characterize QOL trajectories in knee OA. Design: This prospective cohort study included 1013 individuals with symptomatic knee OA from the osteoarthritis initiative. We used group-based trajectory modeling to identify distinct temporal patterns of change in the Knee Injury and Osteoarthritis Outcome Score QOL subscale for 8 yrs. Baseline covariates included age, sex, ethnicity, education, co-morbidities, body mass index, substance use, depression, knee pain, and functional tests. Results: Group-based trajectory modeling revealed the following three distinct QOL trajectories: a high QOL trajectory (32% of the cohort) experiencing improvement for 8 yrs as well as moderate (49%) and low QOL (20%) trajectories maintaining similar levels over time. Low QOL trajectory membership was significantly associated with younger age ( P < 0.001), nonwhite race ( P < 0.001), less education ( P < 0.001), more co-morbidities ( P < 0.001), higher body mass index ( P < 0.001), and more depressive symptoms ( P < 0.001). Higher QOL trajectory members were less likely to undergo knee replacement surgery ( P < 0.001). Conclusions: Distinct QOL trajectories exist in knee OA and are associated with modifiable factors, with a subset of patients showing potential to improve their QOL over time. Abstract : Supplemental digital content is available in the text.